2006
DOI: 10.1097/01.aids.0000222070.52996.76
|View full text |Cite
|
Sign up to set email alerts
|

Fluorodeoxyglucose imaging in healthy subjects with HIV infection: impact of disease stage and therapy on pattern of nodal activation

Abstract: Abnormal fluorodeoxyglucose accumulation occurs in the nodes of individuals with detectable viral loads. Interruption of effective HAART results in the activation of previously quiescent nodal areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 33 publications
1
25
2
Order By: Relevance
“…Our data concur with the findings of previous studies showing that the degree of FDG uptake is related to viral load in reactive adenopathy [3, 28], and we demonstrated a significant correlation between viral load and SUL uptake in HIV-infected patients with reactive adenopathy. This differs from the findings of Brust et al [25], which may have been due to differences in the patient populations, levels of viremia and SUL-Max threshold. We also found lower metabolic uptake in aviremic HIV-infected patients with reactive adenopathy [25].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data concur with the findings of previous studies showing that the degree of FDG uptake is related to viral load in reactive adenopathy [3, 28], and we demonstrated a significant correlation between viral load and SUL uptake in HIV-infected patients with reactive adenopathy. This differs from the findings of Brust et al [25], which may have been due to differences in the patient populations, levels of viremia and SUL-Max threshold. We also found lower metabolic uptake in aviremic HIV-infected patients with reactive adenopathy [25].…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have shown a positive linear relationship between viral load and SUV of the whole-body lymphoid tissue in HIV-infected patients. A more variable relationship is seen between viral loads when regions of interest are manually drawn to obtain total lymph node SUV [25]. …”
Section: Discussionmentioning
confidence: 99%
“…In a study reported by Castaigne et al [23] FDG-PET was able to detect disseminated tuberculosis in HIV-positive patients who showed atypical signs and were difficult to diagnose. In our HIV-positive patients, Castleman disease and Kaposi's sarcoma were identified as true-positive results and systemic aspergillosis was identified as a false-negative result, in addition to three true-positive results in HIV patients with systemic nodal activation [24].…”
Section: Discussionmentioning
confidence: 61%
“…In patients with active sarcoidosis, significant uptake is seen at the disease sites and can be mistaken for lymphoma or other lymphoproliferative disorders. (24). In AIDS patients, toxoplasmosis is the most common opportunistic infection, and the CNS is the most common site for this infection (128).…”
Section: Soft Tissue Infectionmentioning
confidence: 99%